A Gap Analysis of Tourists' Expectations and Satisfaction Using the SERVQUAL Model on a Farm Tourism in Bulacan, Philippines - Veranga, Maricar A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The main purpose of the study is to analyze the gap of tourists’ expectations and satisfaction on a Farm Tourism in Bulacan using the five dimensions of SERVQUAL. The 219 respondents were tourists of the farm and they were conveniently selected. Data were further subjected to ANOVA and T – test analysis via SPSS. Findings revealed that the majority of the respondents belong to the Gen Z individuals. With a gap of 0.15, it was determined that the farm tourism site provides the appropriate level of quality service in terms of tangibility, responsiveness, reliability, assurance, and empathy. The result shows that farm tourism manages to exceed the set expectation level of the tourist in their service quality based on gap from their satisfaction level. Moreover, the tourist gap was significantly equal for both male and female respondents. The total satisfaction is significantly higher compared to their total expectation with a mean difference of 0.16 in favor of the satisfaction level. The null hypothesis was rejected and concluded the gap between tourist’ expectation and satisfaction on the farm tourism service quality when they are grouped according to profile are significantly equal